Effects of students’ psychological needs satisfaction on interprofessional competencies: a multilevel analysis - Xiaoai Shen; John Ian Wilzon T. Dizon; George L. Tipoe; Fraide A. Ganotice (BMC Medical Education)
Abstract Background Interprofessional education (IPE) promotes learning across different disciplines in a team-based learning format. However, existing research has not examined the influence of psychological needs satisfaction at the team level on interprofessional competencies, representing a critical theoretical and methodological gap. Grounded in self-determination theory (SDT), this study tested the effects of psychological needs (autonomy, competence, relatedness) satisfaction at the individual and team levels on interprofessional competencies (communication, roles and responsibilities, collaborative patient/family-centered approach, conflict management/resolution, and team functioning). Methods This quantitative research involved teams of 7–10 healthcare students from two universities in Hong Kong, including Chinese Medicine, Engineering, Law, Medicine, Nursing, Pharmacy, and Social Work. These students completed the self-reported Basic Psychological Need Satisfaction scale and Interprofessional Collaborative Competencies Attainment Survey after participating in the IPE. Data were analyzed using multilevel analysis. Results Among the psychological needs, autonomy and relatedness at the individual level were critical for developing interprofessional competencies, such as communication, roles and responsibilities, collaborative patient/family-centered approach, conflict management/resolution, and team functioning. Additionally, competence at both individual and team levels emerged as the strongest predictor of collaboration. Conclusions Satisfaction of students’ psychological needs at the individual and team levels is critical for the achievement of interprofessional competencies. Theoretically, adopting SDT as a framework provides IPE implementers an understanding of how satisfaction of basic psychological needs is linked with interprofessional competencies. Practically, our findings can guide the design and implementation of IPE programmes, enhancing collaborative healthcare practice. Methodologically, this study advances IPE literature by utilizing the multilevel analytical approach to identify predictors of IPE competencies at both the student and team levels.